Regional Disparity and Determinants of Body Mass Index Status among Tribal Women in Eastern India - Bichitra Shit; Jagannath Behera; Subhadip Mandal (Indian Journal of Public Health)
The body mass index (BMI) is a commonly employed metric for determining the nutritional status and health risks associated with weight. Tribal women in India face neglect and discrimination in terms of livelihood, nutrition, education, wealth, and health-care access. The study examined 18,697 tribal women from Bihar, West Bengal, Jharkhand, and Odisha, using data from the National Family Health Survey-5. Multinomial logistic regression has been used to determine how the multiple background factors are associated with the BMI of tribal women. The study found that the prevalence of underweight and overweight was 28.5% and 7.6% among tribal women, respectively. Rural tribal women had a higher likelihood of being underweight, whereas urban women were more likely to be overweight. Odisha had a higher prevalence of underweight tribal women, whereas the prevalence is lower in Bihar. The higher prevalence of underweight among tribal women is alarming and necessitates a reconsideration of health infrastructure in the tribal areas.